PERAN KEPALA SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN PERSPEKTIF KONSEP MANAJEMEN MUTU TERPADU STUDI KASUS MAN GUMAWANG KABUPATEN OKU TIMUR - Dedi Arianto (Conciencia, 2014)
AbstractThis type of research is the use of qualitative research. Gumawang MAN head of research subjects using interviews, observation, and documentation. The results showed that the head of MAN Gumawang East OKU District has run aspects of Integrated Quality Management Concept among which are the First, the role as head of MAN Gumawang quality planning coordination to the entire staff of employees and also the board of teachers in conducting activities, involving all components, explains objectives to be achieved, forming committees, monitoring and held meetings every want to do activities. Second, the role as head of quality control MAN Gumawang in this case are Drs. Veri Yulianto undertaken an evaluation of performance, comparing actual performance with targets, holding monthly meetings, specially in setting standards of performance, reward and panishment, provides guidance to employees, asking for a report after activity and always provide motivation to Setaf council employees and teachers. Third, the role of quality improvement in this case the head of MAN Gumawang conduct continuous improvement, conduct supervision per each semester, providing training and education to teachers and employees, held on the hour tutoring students outside of school and work closely with parents.Inhibiting factors Head MAN Gumawang in improving the quality of education is subordinate still less responsive to work productively, his lack of educators / teachers remain, learning tools that have not been beautiful, different subordinate character and limited funds available. While the factors driving or supporting the Head of MAN Gumawang in improving the quality of education consists of an internal factor is the encouragement of inner head MAN Gumawang to always excel, ability and attitude to the task, and the external factor is the support of all components of the madrasa including school committees and community conditions to support. Keywords: Role of the Principal, Education Quality Improvement and Quality Management Concept.